Synergistic rewiring of carbon metabolism and redox metabolism in cytoplasm and mitochondria of aspergillus oryzae for increased l-Malate production - Liu,J; Li,J; Liu,Y; Shin,H-D; Ledesma-Amaro,R; Du,G; Chen,J; Liu,L (ACS Synthetic Biology, 2018)
l-Malate is an important platform chemical that has extensive applications in the food, feed, and wine industries. Here, we synergistically engineered the carbon metabolism and redox metabolism in the cytosol and mitochondria of a previously engineered Aspergillus oryzae to further improve the l-malate titer and decrease the byproduct succinate concentration. First, the accumulation of the intermediate pyruvate was eliminated by overexpressing a pyruvate carboxylase from Rhizopus oryzae in the cytosol and mitochondria of A. oryzae, and consequently, the l-malate titer increased 7.5%. Then, malate synthesis via glyoxylate bypass in the mitochondria was enhanced, and citrate synthase in the oxidative TCA cycle was downregulated by RNAi, enhancing the l-malate titer by 10.7%. Next, the exchange of byproducts (succinate and fumarate) between the cytosol and mitochondria was regulated by the expression of a dicarboxylate carrier Sfc1p from Saccharomyces cerevisiae in the mitochondria, which increased l-malate titer 3.5% and decreased succinate concentration 36.8%. Finally, an NADH oxidase from Lactococcus lactis was overexpressed to decrease the NADH/NAD+ ratio, and the engineered A. oryzae strain produced 117.2 g/L l-malate and 3.8 g/L succinate, with an l-malate yield of 0.9 g/g corn starch and a productivity of 1.17 g/L/h. Our results showed that synergistic engineering of the carbon and redox metabolisms in the cytosol and mitochondria of A. oryzae effectively increased the l-malate titer, while simultaneously decreasing the concentration of the byproduct succinate. The strategies used in our work may be useful for the metabolic engineering of fungi to produce other industrially important chemicals.